Popular financial report for the city of Los Angeles 2022 (European journal of volunteering and community-based projects, 2023)
This report analyzes different financial, economical and social aspects regarding the city of Los Angeles useful to take a broad look at the city to file a Popular Financial Report.
Keywords: Los Angeles; POP